THE EFFECT OF THERMOCYCLING TEST ON THE SURFACE HARDNESS VALUE OF BULK FILL RESIN COMPOSITE - Puspitasari, Dewi; Khairima, Amina; Diana, Sherli (Dentino, 2017)
Background: Bulk fill typed composite resin can be applied at once into the tooth cavity ofapproximately 4 mm. The surface hardness of composite resin can be affected by temperature. Variationtemperature in oral cavity due to the consumption of cold and hot food or beverages. Thermocycling tests areused to simulate aging of restorative materials in oral cavity by exposing material to repeated cycles of cold(4oC) and hot(60°C) temperatures. Purpose: To analyze thermocycling test effect with 1500 and 3000 cycles to thesurface hardness value bulk fill composite resin. Methods: This study is true experimental post test only withcontrol group design. This study used 27 samples of bulk fill composite resin divided into 3 groups, first group iscontrol group that did not do thermocycling test, second group is group of thermocycling 1500 cycles and thirdgroup of thermocycling 3000 cycles. Results: Mean value of composite resin surface hardness control group46.529 ± 1.331 MPa, group thermocycling 1500 cycles 44.100 ± 1.039 MPa, and group thermocycling 3000cycles 42.251 ± 1.470 MPa. The data were tested using One Way ANOVA and post Hoc Bonferroni with p<0.05, there were significant differences in all treatment group. Conclusion: Thermocycling test with 1500 and3000 cycles (equal with clinically used 6 month and 1 year) in resin composites may decrease surface hardnessvalue